Analisis Model Pencegahan Fraud di KSPP Syariah BMT NU Cabang Torjun - Faisol, Faisol; Nizarul Alim, Mohammad (ILTIZAM Journal of Shariah Economics Research, 2024)
The purpose of this research is to describe the fraud prevention model at the BMT NU Torjun branch. This study uses a qualitative method of intrinsic case study approach. Data collection in this study was carried out through interviews, observation, and documentation. From the findings of this study, it can be concluded that the fraud prevention model at the BMT NU Torjun branch starts with the BMT NU managers, who must comply with the SOP provisions that have been set within the BMT NU Torjun branch. To prevent fraud at the Torjun branch of the BMT NU institution, an internal audit is carried out by the central RKM team twice a month on the second weekend. Furthermore, the fraud prevention model at the BMT NU Torjun branch has strict supervision from several parties, including area managers, DPS, and the center. So that with the prevention of fraud established in the BMT NU institution environment, the Torjun branch will provide effective benefits to minimize the occurrence of acts of fraud.